Examining energy uncertainty in battery bus deployments for transit agencies in California. (September 2021) - Benoliel, Peter; Jenn, Alan; Tal, Gil
Highlights: We present a tool to study the optimal infrastructure for an electric bus network. These networks are highly sensitive to vehicle energy use. Maintaining reliability may require a large fleet if other changes aren't made. Investment in saving energy use in electric buses yields a higher return than conventional buses. Abstract: Due to the adoption of the Innovative Clean Transit (ICT) regulation, California is transitioning its public transit buses from fossil fuel to zero-emission buses (ZEBs). Due to required high upfront investment for battery electric buses (BEBs), transit agencies must make planning decisions with a system-wide optimization mindset. This study presents a tool to investigate the optimal split between depot charging and opportunity charging for transit networks. A case study was performed on the Unitrans transit system in Davis, California, and it was found that 35 buses would be sufficient to provide the existing level of service over the bus network, which is approximately the same number of buses that Unitrans is currently using to serve those routes. The sensitivity of the relationship between the energy use of BEBs and the deployment decisions was investigated. Decreasing the energy use of the buses by removing the probabilistic effects of drive cycle aggression decreased the maximum required number of buses from 73 to 45 and the interquartile range (IQR) of the number of buses from 10 to 2. The results indicate that a BEB fleet is more sensitive to these changes than a fossil fuel fleet. This relationship needs to be more strongly considered in planning BEB deployments.